Profil Demografi, Riwayat Kesehatan, dan Rekreasi Aktifitas Pasien Lansia di Jawa Tengah - Nina Indriyawati; Supriyadi Supriyadi; Heru Supriyatno (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
The research aims to describe the demographic profile, medical history, and recreation activity of elderly patients. This research is a descriptive study conducted in elderly patients whose outpatient and inpatient in hospital in Central Java. Samples recruited by purposive sampling during September to November. Number of study subjects obtained during data collection amounted to 128 elderly. Research instrument uses Elderly Demographic Questionnaire. Data were analysed with descriptive statistic. Most of the elderly are male (64%), aged between 60-65 (27%), the type of the funding is using universal coverage (63%), mostly the past education is primary school (41%). Based on the medical history of elderly, 53% have the disease disorder, a diagnosis that often arises is respiratory disorders (19%) and cardiovascular (17%). For operating experience in the past 12 months, most are due to cancer (15%). The TV becomes the main source of information (79%), and TV becomes recreational activity and rest (56%), and 62% of elderly participated in religious activities. The need for activities that support the income of elderly or increase it. The need for social activities that also give benefit recreation and exchange of information.